2011
DOI: 10.1103/physrevb.83.104521
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium effects in a Josephson junction coupled to a precessing spin

Abstract: We present a theoretical study of a Josephson junction consisting of two s-wave superconducting leads coupled over a classical spin. When an external magnetic field is applied, the classical spin will precess with the Larmor frequency. This magnetically active interface results in a time-dependent boundary condition with different tunneling amplitudes for spin-up and spin-down quasiparticles and where the precession produces spin-flip scattering processes. We show that as a result, the Andreev states develop s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 86 publications
(158 reference statements)
2
57
0
Order By: Relevance
“…Furthermore, the dynamics of both JJs with misaligned ferromagnetic layers and those coupled to single or multiple ferromagnetic layers have also been studied numerically 31 . It has also been shown that the presence of a single classical spin of a molecular magnet precessing under the action of a constant magnetic field coupled to a JJ may lead to generation of finite spin current whose polarization axis rotates with same frequency as the classical spin 32 . Such theoretical studies were complemented by experimental work on these systems 33 .…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Furthermore, the dynamics of both JJs with misaligned ferromagnetic layers and those coupled to single or multiple ferromagnetic layers have also been studied numerically 31 . It has also been shown that the presence of a single classical spin of a molecular magnet precessing under the action of a constant magnetic field coupled to a JJ may lead to generation of finite spin current whose polarization axis rotates with same frequency as the classical spin 32 . Such theoretical studies were complemented by experimental work on these systems 33 .…”
Section: Pacs Numbersmentioning
confidence: 99%
“…[41]. More suitable approaches for current calculation lead to singularities instead of divergences [28,29]. These singularities are consequence of the singular BCS density of states at the gap edges and are signatures for contribution of an infinite number of extended states in the current.…”
Section: Resultsmentioning
confidence: 99%
“…In Refs. [29,30] it has been shown that when the nanomagnet undergoes a precession due to an external magnetic filed the Andreev levels are affected by the dynamics of the nanomagnet's spin. The resultant Andreev levels depend on the tilt angle and precession frequency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations